THE IMPLEMENTATION OF 5S MANAGEMENT AT OFFSET UNIT: CASE STUDY AT PT PURRA BARUTAMA, KUDUS - Tamado Simbolon; MT Djamara; Antinah Latif (Politeknik Negeri Media Kreatif, 2020)
Companies that have poor performance can be seen from the irregular work situation, the number of project items or reworks, the bad employee attendance scores and so on. How to implement the 5R, because the 5R is a management system in maintaining order, efficiency and discipline in the workplace, as well as increasing overall company performance. 5R is the first indicator to assess the good and bad performance of a company. However, it is unfortunate that not all companies understand the importance of (K3) and how to implement it in a corporate environment. The writing method used is descriptive method. The purpose of writing: To determine employee understanding of the 5R program in Occupational Safety and Health, to determine the implementation of the 5R program in Occupational Safety and Health which is run at PT. Pura Barutama Kudus Offset Unit, to find out the implementation of the 5R program in controlling Occupational Safety and Health which is carried out by PT Pura Barutama Kudus Offset Unit. Based on the observation that 5R management must always be improved.Keywords: 5S, OHS, Printing Industry